Antecedents of Public Service Motivation of Muslim-Majority Countries in Southeast Asia (Indonesia and Malaysia) - Dewi, Dian Suluh Kusuma; Nurmandi, Achmad; Mutiarin, Dyah; Manaf, Halimah Abdul; Hidayati, Mega; Sulthon,; Harsono, Jusuf (International Journal of Psychosocial Rehabilitation, 2020)
The role of socio-historical is the Public Service Motivation (PSM) attachment brought by James Perry. 4 dimensions of PSM are associated with parental socialization, religious socialization, professional identification, and political ideology. This article examines Perry's findings by including volunteerism in two regional governments in the majority of Muslim countries namely Yogyakarta, Indonesia and Kedah, Malaysia. By using Qualitative methods, primary data were obtained from in-depth interviews with 8 informants. Infromant were randomly selected using the characteristics of 1) must be Muslim; 2) work in public organizations for more than 2 years and 3) are staff-mid level officials. Secondary data is the result of observations, and online media reporting documents through the official website of the Yogyakarta special government agency and the Kedah Malaysian government agency. Data analysis methods used Nvivo 12 plus. This article explains that there are differences in PSM determinant factors in Moslem majority countries. Religious socialization has the most influence in Malaysia, while voluntarism in Indonesia. This difference is driven by different cultural backgrounds, incomes, and governance systems.